"Role of Lectins in Interaction Between Parasites and the Important Insect Vectors" - HR Basseri (Tehran University of Medical Sciences, 2002)
There is growing evidence that lectin-carbohydrate interactions can mediate the infection of parasites to their insect vector. Many insect species are host or vectors of protozoan or metazoan parasites that cause socially and economically important disease such as malaria and leishmaniasis. However, relatively little work has been undertaken concerning the interaction of insect immunity against parasite invasion with respect to lectins activities. Both immune defences (cellular and noncellular) of insect haemolymph react in order to combat the diverse array of natural pathogens and other microorganisms. The most of immune substances are innate, naturally-occurring and nonspecific molecules present in haemolymph. When the physical defences of the insect gut or integument are breached by an invading organism an innate response begins, characterized by immune system's agents such as coagulation, melanization, phagocytosis, encapsulation and nodule formation. Nevertheless, in many cell types such as insect haemocytes, carbohydrates are known to be crucially involved in cell-cell interactions and many studies have addressed the role of carbohydrates and carbohydratebinding molecules in the adhesion of parasites to their host. As mentioned above, one candidate for attachment and invasion may be lectins or lectinlike molecules that are known to mediate cell-to-cell interaction. In order to the basic understanding of pathogens transmission by vectors, in this article, the interaction between parasites and insect vectors has been reviewed with respect to role of lectins molecules.